Eccentric Exercise Intervention is Better Than Active Static Stretching for Increasing Hamstring Muscle Flexibility and Agility in Futsal Players at Bali Bulldogs Football Club - Amarilis Brensiline Sekar Kinasih; Indira Vidiari Juhanna; Syahmirza Indra Lesmana (International Journal of Public Health Excellence (IJPHE), 2026)
Futsal requires high hamstring flexibility and agility for peak performance and injury prevention. Players often face muscle shortening and reduced agility, which can negatively impact their game. Active static stretching is a common method for improving flexibility, but eccentric exercise holds significant promise for increasing muscle length and strength, which are vital for both preventing muscle shortening and boosting agility. This study aimed to compare the effectiveness of these two scientifically-backed interventions, as direct comparisons in futsal players are limited. Using a quasi-experimental pre-test and post-test design, 22 male futsal players (aged 18-25) were divided into two groups: one for active static stretching and one for eccentric exercise. The interventions were performed three times a week for six weeks. Flexibility was assessed with the Active Knee Extension Test (AKET), while agility was measured using the Illinois Agility Test. The data were analyzed using paired simple t-tests and independent t-tests. The results showed that both interventions improved flexibility and agility (p<0.05). However, eccentric exercise was significantly more effective. The eccentric exercise group showed a greater increase in flexibility (mean difference: -3.409 ± 1.0521) compared to the active static stretching group (mean difference: -0.482 ± 0.1722), with a p-value of 0.000. Similarly, agility improved more in the eccentric exercise group (mean difference: -1.127 ± 0.4452) than in the active static stretching group (mean difference: -0.282 ± 0.1168), also with a p-value of 0.000.In conclusion, eccentric exercise is more effective than active static stretching for enhancing hamstring flexibility and agility in futsal players, making it a highly recommended addition to training programs